2012
DOI: 10.1542/peds.2011-2158
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics for Children and Young Adults: A Comparative Effectiveness Review

Abstract: This is the first comprehensive review comparing the effectiveness and safety across the range of antipsychotics for children and young adults. The evidence on the comparative benefits and harms of antipsychotics is limited. Some SGAs have a better side effect profile than other SGAs. Additional studies using head-to-head comparisons are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 98 publications
3
94
0
1
Order By: Relevance
“…SGA treatment for children is often associated with the symptomatic treatment of developmental or other disorders with a long duration (1,2,8,14,21,22,25). The average duration of the SGA medication was long in this study as well: the median duration was almost two years.…”
Section: Discussionmentioning
confidence: 62%
“…SGA treatment for children is often associated with the symptomatic treatment of developmental or other disorders with a long duration (1,2,8,14,21,22,25). The average duration of the SGA medication was long in this study as well: the median duration was almost two years.…”
Section: Discussionmentioning
confidence: 62%
“…13,15 These increases have been mirrored by a dramatic rise in the use of neuropsychiatric drugs in children. [16][17][18] Antipsychotic use increased from 8.6 per 1000 children to 39.4 per 1000 children from 1995 to 2002, for example, and antidepressant use increased from 9.4 per 1000 to 21.3 per 1000 children between 1994 and 2003. [19][20][21] The lack of clinical evidence to support the use of these agents in children has resulted in a number of controversies, including concerns over increased suicidality among adolescents treated with selective serotonin reuptake inhibitors and of antipsychotic side effects in young children.…”
Section: Discussionmentioning
confidence: 99%
“…6,[26][27][28][29] A recent literature review by the Agency for Healthcare Research and Quality found limited evidence for the effectiveness of secondgeneration antipsychotics in the treatment of ADHD. 30 Although concomitant use of LAS and AAPs is common in pediatric settings, little is known about the prevalence of and factors associated with concomitant use of LAS and AAPs in youth with ADHD. Recently, Betts et al (2014) examined the prevalence of concomitant psychotropic medication use in commercially insured children and adolescents with ADHD in the United States to find that AAPs were one of the most commonly prescribed concomitant medications (5.8%-6.8%).…”
Section: ■■ Methods Study Design and Data Sourcementioning
confidence: 99%